2014
DOI: 10.1016/j.nucmedbio.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-centered signaling pathways are effectively activated during low dose-rate Auger radioimmunotherapy

Abstract: Hypersensitivity to non-internalizing (125)I-mAbs is not due to lack of detection of DNA damage after low absorbed dose-rates. However, DNA double strand breaks accumulate in cells exposed both to internalizing and non-internalizing (125)I-mAbs and lead to micronuclei formation. These results suggest impairment in DNA double strand breaks repair after low absorbed doses of (125)I-mAbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…ROS contribute to “chronic” oxidative stress and the subsequent DNA damage, including the formation of micronuclei in nontargeted cells ( 3 , 44 ). This is in agreement with our previous finding that the abundance of micronuclei in cells exposed to 125 I-mAbs was not correlated with the mean absorbed dose to the nucleus ( 48 , 50 ). The involvement of oxidative stress in EBRT-induced nontargeted effects has been extensively reviewed by Havaki et al ( 20 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ROS contribute to “chronic” oxidative stress and the subsequent DNA damage, including the formation of micronuclei in nontargeted cells ( 3 , 44 ). This is in agreement with our previous finding that the abundance of micronuclei in cells exposed to 125 I-mAbs was not correlated with the mean absorbed dose to the nucleus ( 48 , 50 ). The involvement of oxidative stress in EBRT-induced nontargeted effects has been extensively reviewed by Havaki et al ( 20 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the cytotoxicity of noninternalizing mAbs was greater than that achieved by internalizing 125 I-mAbs ( 50 , 53 ) and was not due to inefficient detection of DNA damage related to low absorbed dosage. We proposed that, instead, nontargeted effects could be involved ( 48 ). This is in agreement with the work by Xue et al in 2002 showing in vivo that nontargeted effects are produced by LS174T cells radiolabeled with the DNA base analog 5-[(125)I]iodo-2′-deoxyuridine ( 125 I-UdR), indicating that Auger electrons can kill cells beyond their path length ( 66 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the highly localized energy deposition associated with Auger electrons and alpha particles is also an attractive tool to investigate the biological effects of ionizing radiations at the subcellular scale and has shown the weaknesses of a completely DNA-centered conception of TRT effects. Indeed, we and others have demonstrated that extra-nuclear targets are also involved in targeted and non-targeted responses ( 74 78 ). The existence of non-targeted effects may affect the absorbed dose–effect relationship.…”
Section: Targeted Radionuclide Therapymentioning
confidence: 89%
“…Several hypotheses have been proposed to explain this effect, including TRT-mediated synchronization of cells in a radiosensitive cell cycle phase or defects in the detection of low levels of DNA damage. However, these mechanisms cannot be generalized ( 78 ) and TRT biology still needs to be investigated for each TRT situation. Models and notions have been developed to reduce the discrepancies between the theoretical dose–effect relationship and the real biological effects measured in human patients using clearly identified endpoints (creatinine values, for example).…”
Section: Targeted Radionuclide Therapymentioning
confidence: 99%
“…20 225 Ac decays into 4 alpha-emitting daughter particles, 2 of which emit an imageable gamma ray, and 225 Ac-radiolabeled full length antibodies have been efficacious in tumor-cell killing in in vitro and in vivo preclinical studies, 21,22 as well as clinical studies. 3,23 Auger emitters, such as 125 I, have low energy and are considered to have high LET (4-26 keV/μm) with a very short path length of 2-500 nm 24 (Figure 2). Similar to alpha emitters, Auger emitters may be more suitable for limiting damage to normal tissues compared with betaemitters 25 ; however, strategies must be devised for intracellular delivery, preferably in the vicinity of the cell nucleus.…”
Section: Radionuclides For Imaging and Therapymentioning
confidence: 99%